Potensi Ekstrak Etanol 96% Daun Salam (Syzigium polyanthum Wight. (Walp.)) terhadap Ekspresi p53 pada Sel Kanker HeLa Cell Lines - Hidayati, Wahyu; Sjahid, Landyyun Rahmawan; Ismalasari, Wahyu; Kusmardi, Kusmardi (Jurnal Kefarmasian Indonesia, 2020)
Bay leaves (Syzigium polyanthum Wight. (Walp.) have been utilized as one of traditional medicines in Indonesian. However, the potency of the leaves for cancer treatment has not been well-explored. The aim of this study is to determine the expression of p53 tumor suppressor gene after administration of 96% ethanol extract of Bay leaves on HeLa cell lines. This study is begin by making extract using ethanol 96% as a solvent followed by phytochemical screening and extract evaluation of HeLa cells by immunohistochemistry. The observation of p53 protein expression is conducted using the Image J Profiler Plugin software 1.52a version. The H-score data is processed using the One-Way ANNOVA IBM SPSS 20 version program and continued with Post Hoc analysis using the Duncan test. The identification of 96% ethanol extract result showed that bay leaves contain flavonoids, alkaloids, saponins, phenols, terpenoids, and steroids. Based on the Post Hoc test results, the administration of 96% ethanol extract bay leaves with three dose variations (156 µg/ml, 234 µg/ml, 312 µg/ml) and negative control had significant differences, while the high dose (312 µg/ml) had not significant differences to positive control. The result showed that 96% ethanol extract of bay leaves by the dose of 312 ug/ml can inhibit the expression of mutant p53 protein in cervical cancer cells HeLa cell lines.